(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
As a participant in the 2010 International Institute on Peace Education (IIPE) which was held in Cartagena, Colombia, I had the opportunity to facilitate a workshop relevant to the field of peace education. When the time came to propose a workshop, I had no difficulty deciding what I wanted to share with other educators, peace activists, individuals from non-profit and non-governmental organization, and academics. At the IIPE I facilitated a workshop on participatory artistic quiltmaking for peacebuilding and peace education that was based on my Master of Arts research conducted in Vancouver, British Columbia, Canada, on the role of participatory artistic quiltmaking for peacebuilding and peace education among youth aged 8 to 12. This paper presents a narrative of what occurred in the IIPE workshop as well as explains participatory artistic quiltmaking in the context of peacebuilding. The paper also highlights some initial findings from my Master of Arts research and describes the use of participatory artistic quiltmaking in research.